Nurses’ perception of anticipated nursing care: A qualitative research - Khadijeh Dehghani; Imane Bagheri; Atena Dadgari; Naiire Salmani (PLoS ONE, 2025)
Background Anticipated nursing care is provided significantly earlier than expected by nurses, caregivers, and other healthcare staff for patients. This type of care is influenced by many factors and is followed by various positive and negative consequences. Accordingly, the present study sought to explore nurses’ perceptions of anticipated nursing care. Methods This qualitative study was conducted using content analysis on twelve nurses from different internal and surgical wards of Shahid Sadoughi Hospital, Yazd, Iran from November 2022 to September 2023The participants were selected using purposive sampling. The data were collected through semi-structured interviews with the nurses and analyzed using Graneheim and Lundman’s qualitative content analysis method. Results Data analysis revealed four main categories and eleven subcategories. The main categories included early and priority care with two subcategories, scope of anticipated care with four subcategories, predictors of anticipated care with three subcategories, and outcomes of anticipated care with two subcategories. Conclusions Based on the findings, it is suggested that nursing managers must focus on the antecedents of anticipated care and address strategies to improve the working conditions of nurses, changing routine procedures for providing care and the doctor-nurse interaction, developing and organizing training programs on clinical reasoning, decision-making and time management for nurses.